Confessions of a Reluctant Publisher. - Lyons, Nick (Antioch Review)
This article discusses the author's experience of working as an independent publisher. The author, after working at Crown Publishers, has decided to become an independent publisher. He encounters several challenges of being on his own, without support systems from Crown. He has to do the editing, composition, design and sales all by himself. His has raised money from his friends. His children have helped him collect money, sold rights and arrange index cards among others. Some time he doubted if his business could survive but it did.